Defeasible knowledge - Moeller, E (2014)
This dissertation collects five papers that discuss potential consequences of the defeasibility of knowledge. Chapters 1, 2, 3, and 5 provide arguments for a number of important epistemological consequences of the defeasibility of knowledge. Chapter 4 discusses consequences that others have claimed the defeasibility of knowledge to have. Chapter 1 argues that closure principles for knowledge are in tension with the defeasibility of knowledge. Chapter 2 argues that one of Williamson's famous arguments against the KK principle relies in a problematic way on a closure principle that is incompatible with defeat. Chapter 3 argues that a view on which knowledge just is belief safe from error is in tension the defeasibility of knowledge. Chapter 4 discusses two arguments to the effect that defeat by higher-order evidence sometimes involves the violation of rational ideals or rules of rational belief formation. As part of a response to an objection to contextualism about 'know', Chapter 5 investigates a number of social epistemological consequences of the defeasibility of knowledge.